Realization of multi-material polymer parts by simultaneous laser beam melting - Laumer, Tobias; Stichel, Thomas; Riedlbauer, Daniel-Rouven; Amend, Philipp; Mergheim, Julia; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2015)
In this paper, first results regarding the realization of multi-material parts by Simultaneous Laser Beam Melting (SLBM) of polymers are presented. This new approach allows the layerwise generation of parts consisting of different polymer materials within one building process. Besides the typical advantages of additive manufacturing technologies, such parts can fulfill different product requirements concomitant and therefore could enlarge the overall field of application. The powder materials used for this paper are polyethylene (PE) and a polyamide based thermoplastic elastomer (TPE). After depositing the powder materials next to each other, infrared-emitters heat the lower melting polymer and a CO2 laser provides the preheating temperature of the higher melting polymer. In the last step, a thulium fibre laser melts the two preheated powders simultaneously. The realized specimens are characterized by cross sections and their tensile strengths are determined. Additionally, the new approach of the simultaneous energy irradiation is investigated using a Finite Element Analysis in order to gain a more profound process understanding. In that sense, the influence of the size of the exposure area on the reachable maximum temperatures inside that area was analyzed by the simulation and compared to experimental studies.
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-TM.realiz
Keywords: Additive manufacturing; Multi-material parts; New materials; Simultaneous laser beam melting of polymers